Antigen Reactivity and Clinical Significance of Autoantibodies Directed Against the Pyruvate Dehydrogenase Antigen Complex in Patients With Connective Tissue Disease - Ceribelli, Angela; Isailovic, Natasa; Gorlino, Carolina; Assandri, Roberto; Vecellio, Matteo; De Santis, Maria; Satoh, Minoru; Selmi, Carlo (Frontiers in Immunology, 2022)
Introduction. Anti-mitochondrial antibodies (AMA) are the hallmark of primary biliary cholangitis (PBC), but can be identified also in patients with connective tissue disease, namely systemic sclerosis (SSc). Protein-immunoprecipitation (IP) and IP-Western Blot (WB) can be used to confirm AMA positivity directed at the pyruvate dehydrogenase complex (PDC) subunits E1α, E1β, E2/E3, and E3BP, in patients showing a cytoplasmic reticular pattern at indirect immunofluorescence, when performed in a screening setting before the onset of overt cholestasis in rheumatic patients. Patients and methods. We studied sera from 285 patients affected by connective tissue disease (SSc, n=144; dermato/polymyositis- DM/PM, n=56; and undifferentiated connective tissue disease- UCTD, n=85) by IIF, protein-IP and IP-WB to identify specific PDC subunits recognized by AMA. Results. Twenty % (57/285) of sera from patients with connective tissue disease had a cytoplasmic reticular pattern at IIF and in 77% (44/57, including 20 SSc, 12 PM/DM, and 12 UCTD) of these we detected different titers of autoantibodies against the PDC subunits, specifically against PDC-E2. Among these sera, 4 (9%) tested positive for anti-E1α, 15 (34%) for anti-E1β, 16 (36%) for anti-E3BP. Four of the 20 AMA-positive SSc cases (20%) had been already diagnosed with PBC and all were positive for autoantibodies against the subunits PDC-E2, E3, and E3BP. Conclusions. Using indirect immunofluorescence and immunoprecipitation, we confirm that autoantibodies against the PDC components are detected in rheumatic patients with PBC or without liver dysfunction. In view of the strong predictive value of AMA for PBC, a strict follow-up of these latter patients is warranted for an early diagnosis of the disease.